American Joint Committee on Cancer Eighth Edition Changes in Staging Criteria: Implications for Data Collection. (25th July 2017) - Saraswathula, Anirudh; Chen, Michelle; Negoita, Serban; Divi, Vasu
Abstract : The American Joint Committee on Cancer, in the eighth edition of its cancer staging manual, makes a number of changes to improve survival predictions in human malignancy. In this commentary, we examine the national collection of data for head and neck cancer. We outline and review the major changes made in head and neck cancer staging, identify the key data elements that will need to be collected with the new edition's criteria, and discuss the institutional adjustments currently being made to data collection under the new guidelines to improve the quality of data in our national cancer databases.